2019
DOI: 10.1073/pnas.1914180116
|View full text |Cite
|
Sign up to set email alerts
|

Directional coupling of slow and fast hippocampal gamma with neocortical alpha/beta oscillations in human episodic memory

Abstract: SignificanceEpisodic memories detail our personally experienced past. The formation and retrieval of these memories have long been thought to be supported by a division of labor between the neocortex and the hippocampus, where the former processes event-related information and the latter binds this information together. However, it remains unclear how the 2 regions interact. We uncover directional coupling between these regions, with power decreases in the neocortex that precede and predict power increases in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(135 citation statements)
references
References 61 publications
14
116
1
Order By: Relevance
“…This effect may be determined because of direct connections (via entorhinal cortex) with regions supporting the formation of contextual memories, such as in the parahippocampal gyrus and the hippocampus (Bar et al, 2008;Davachi, 2006;Dundon et al, 2018). A recent study has demonstrated the interplay between semantic processing in ATL and information encoding/retrieval in the hippocampus during the formation/retrieval of contextual memories (Griffiths et al, 2019). Accordingly, it is possible that these anatomical connections allow these regions to cooperate for the formation and retrieval of semantic and contextual information conveyed in the narrative (e.g., episodic details) (Ranganath and Ritchey, 2012), facilitating the flow of neocortical information into the hippocampus during encoding and the propagation of hippocampal retrieval signals into the ATL during retrieval.…”
Section: Hubs For the Formation Of Time-extended Conceptual Gestaltmentioning
confidence: 99%
“…This effect may be determined because of direct connections (via entorhinal cortex) with regions supporting the formation of contextual memories, such as in the parahippocampal gyrus and the hippocampus (Bar et al, 2008;Davachi, 2006;Dundon et al, 2018). A recent study has demonstrated the interplay between semantic processing in ATL and information encoding/retrieval in the hippocampus during the formation/retrieval of contextual memories (Griffiths et al, 2019). Accordingly, it is possible that these anatomical connections allow these regions to cooperate for the formation and retrieval of semantic and contextual information conveyed in the narrative (e.g., episodic details) (Ranganath and Ritchey, 2012), facilitating the flow of neocortical information into the hippocampus during encoding and the propagation of hippocampal retrieval signals into the ATL during retrieval.…”
Section: Hubs For the Formation Of Time-extended Conceptual Gestaltmentioning
confidence: 99%
“…Probing rat hippocampal neurons in vitro, Bi and Poo (1998) showed that the postsynaptic neuron must fire 20 ms (that is, 1 cycle of a gamma oscillation) after the presynaptic neuron to induce LTP. Given that these hippocampal neurons have been shown to lock gamma-band activity (Jutras, Fries, & Buffalo, 2009) and hippocampal gamma-band activity is predictive of memory formation (e.g., Griffiths et al, 2019;Long & Kahana, 2015), one could speculate that increases in the amplitude of hippocampal gamma oscillations reflect increases in STDP.…”
Section: A Role For Neural Oscillationsmentioning
confidence: 99%
“…A memory-related increase in synchronisation can take the form of an increase in theta or gamma power (e.g. Burke et al, 2013;Griffiths, Parish, et al, 2019;Long & Kahana, 2015;Montgomery & Buzsáki, 2007;Osipova et al, 2006;Sederberg et al, 2007;Staresina et al, 2016), or an increase in the coupling between these two oscillations (e.g. Bahramisharif, Jensen, Jacobs, & Lisman, 2018;Heusser, Poeppel, Ezzyat, & Davachi, 2016;Staudigl & Hanslmayr, 2013;Tort, Komorowski, Manns, Kopell, & Eichenbaum, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…By coupling gamma power to the phase of theta that is optimal for LTP, the propensity for mnemonic binding is further enhanced. However, hippocampal activation during encoding is contingent on the amount of preceding neocortical desynchronisation, and vice versa during episodic memory retrieval (Griffiths, Parish, et al, 2019). Statistically speaking, it is therefore plausible to suggest that a single latent variable produces both neocortical desynchronisation and hippocampal synchronisation.…”
Section: Introductionmentioning
confidence: 99%